Isker as a Mythologeme in the Study of Siberian Khanate History » - D.N. Maslyuzhenko; S.F. Tataurov (Золотоордынское обозрение)
Research literature on the history of Siberian Khanate consider Isker not only as a metropolitan center but also as a large and well-fortified town. The analysis of written and archaeological sources shows that such an assumption in many respects developed under the influence of the authors, who described it later, a long time after the abandonment of Isker. They were influenced to a large extent by ideas about how Tatar city might have looked as an ideal model, the embodiment of which they searched on the ruins of the Siberian cities of the 15th–16th centuries. Authors of this work consider that conditions of a fortress location, as well as artifacts, found there, do not confirm this traditional version. Isker came under the authority of Siberian Shibanids (with a throne place situated in Chimgi-Tura (Tyumen)) not earlier than in 1563, after the Siberian people had invited Kuchum ibn Murtaza to become their khan. At the same time, representatives of a dynasty controlled not only the lands in the south of Western Siberia, but also across the Syr Darya. Being natives of a nomadic environment, their center of power was situatetd in nomadic khan’s encampment, from which they moved from summering in the north to wintering grounds in the south. Exactly in this encampment, but not in geopolitically and ecologically uncomfortably located Isker, it is supposed to be the khan’s treasury and the place for his family as well as seyyids and other Muslim preachers. Isker was only a place of collecting the yasak from Ugrian groups of local population during the autumn and spring periods. For these reasons, its protection during Yermak’s attack was not the khan’s priority task. The town was abandoned easily. Isker is not so important for the history of Siberia as for Russian history during the period of incorporation of Siberia into the Muscovy. For the Russian tsars, Isker became a symbol of the legitimacy of power of Ivan the Terrible in Siberia.